Histone Deacetylase Inhibitors and Mithramycin A Impact a Similar Neuroprotective Pathway at a Crossroad between Cancer and Neurodegeneration - Sleiman, Sama F. (MDPI, 2011)
Mithramycin A (MTM) and histone deacetylase inhibitors (HDACi) are effective therapeutic agents for cancer and neurodegenerative diseases. MTM is a FDA approved aureolic acid-type antibiotic that binds to GC-rich DNA sequences and interferes with Sp1 transcription factor binding to its target sites (GC box). HDACi, on the other hand, modulate the activity of class I and II histone deacetylases. They mediate their protective function, in part, by regulating the acetylation status of histones or transcription factors, including Sp1, and in turn chromatin accessibility to the transcriptional machinery. Because these two classes of structurally and functionally diverse compounds mediate similar therapeutic functions, we investigated whether they act on redundant or synergistic pathways to protect neurons from oxidative death. Non-protective doses of each of the drugs do not synergize to create resistance to oxidative death suggesting that these distinct agents act via a similar pathway. Accordingly, we found that protection by MTM and HDACi is associated with diminished expression of the oncogene, Myc and enhanced expression of a tumor suppressor, p21(waf1/cip1). We also find that neuroprotection by MTM or Myc knockdown is associated with downregulation of class I HDAC levels. Our results support a model in which the established antitumor drug MTM or canonical HDACi act via distinct mechanisms to converge on the downregulation of HDAC levels or activity respectively. These findings support the conclusion that an imbalance in histone acetylase and HDAC activity in favor of HDACs is key not only for oncogenic transformation, but also neurodegeneration.